Acute Effects of Handheld Vibration Massage on Posterior Shoulder Soft Tissues - Takaki Imai; Takashi Nagamatsu; Yushin Yoshizato; Kodai Miyara; Megumi Sumizono; Masatoshi Nakamura (International Journal of Sports Physical Therapy)
# Background